High Vascular Delivery of EGF, but Low Receptor Binding Rate Is Observed in AsPC-1 Tumors as Compared to Normal Pancreas - Samkoe, Kimberley S. (2012)
PURPOSE: Cellular receptor targeted imaging agents present the potential to target extracellular molecular expression in cancerous lesions; however, the image contrast in vivo does not reflect the magnitude of overexpression expected from in vitro data. Here, the in vivo delivery and binding kinetics of epidermal growth factor receptor (EGFR) was determined for normal pancreas and AsPC-1 orthotopic pancreatic tumors known to overexpress EGFR. PROCEDURES: EGFR in orthotopic xenograft AsPC-1 tumors was targeted with epidermal growth factor (EGF) conjugated with IRDye800CW. The transfer rate constants (k(e,)K(12), k(21), k(23), and k(32)) associated with a three-compartment model describing the vascular delivery, leakage rate and binding of targeted agents were determined experimentally. The plasma excretion rate, k(e), was determined from extracted blood plasma samples. K(12), k(21), and k(32) were determined from ex vivo tissue washing studies at time points ≥24 h. The measured in vivo uptake of IRDye800CW-EGF and a non-targeted tracer dye, IRDye700DX-carboxylate, injected simultaneously was used to determined k(23). RESULTS: The vascular exchange of IRDye800CW-EGF in the orthotopic tumor (K(12) and k(21)) was higher than in the AsPC-1 tumor as compared to normal pancreas, suggesting that more targeted agent can be taken up in tumor tissue. However, the cellular associated (binding) rate constant (k(23)) was slightly lower for AsPC-1 pancreatic tumor (4.1×10(−4) s(−1)) than the normal pancreas (5.5×10(−4)s(−1)), implying that less binding is occurring. CONCLUSIONS: Higher vascular delivery but low cellular association in the AsPC-1 tumor compared to the normal pancreas may be indicative of low receptor density due to low cellular content. This attribute of the AsPC-1 tumor may indicate one contributing cause of the difficulty in treating pancreatic tumors with cellular targeted agents.